Performance of SNAPPE-II score in neonatal sepsis: an experience from a tertiary care center - Samanta, Moumita; Biswas, Chiranjib; Pal, Nishith Kumar; Sarkar, Soma; Goswami, Avranil; Hazra, Avijit; Bhowmik, Arijit; Sabui, Tapas Kumar (The Turkish Journal of Pediatrics, 2020)
Background and Objectives. The Score for Neonatal Acute Physiology II with Perinatal Extension (SNAPPE-II) is a vital tool for prognostication in newborns. The study was conducted with the hypothesis that the performance of the SNAPPE-II score might be affected by the presence of sepsis in newborns admitted with possible early onset septicemia and whether score performance varies between culture positive and culture negative sepsis. Methods. The prospective observational study was conducted over a period of 1 year (January 2014 to January 2015) in neonates presenting with clinical suspicion of sepsis to the Sick Newborn Care Unit (SNCU) of a tertiary care hospital in Eastern India. Results. SNAPPE-II score cut-off of ≥20 offered the highest sensitivity of 74.5% with specificity 48.3%, PPV 27.6% and NPV 87.7%. Comparison of mortality proportions between the two subgroups defined by this cut-off returned p= 0.005 with OR 3.47 (95% 1.40 to 8.64). No significant association was found between SNAPPE-II score and blood culture results; mean scores for culture positive (25.16 ± 15.6) and negative groups (24.49 ± 15.6) were comparable (p= 0.920). Conclusions. At a cut-off value of ≥20 in presence of sepsis, SNAPPE-II score offers acceptable indices to predict mortality outcome. Prediction of outcome by SNAPPE-II score is not affected by positive or negative blood culture sepsis.
Keywords: SNAPPE score; blood culture; neonatal sepsis